Incorporation of Non-Canonical Amino Acids into Proteins by Global Reassignment of Sense Codons - Fang, Katharine Y; Lieblich, Seth A; Tirrell, David A (Methods in molecular biology (Clifton, N.J.), 2018)
Non-canonical amino acids are finding increasing use in basic and applied research. Proteins that evolved naturally for biological function did so by exploiting the chemistries of the canonical amino acids; however, when proteins are repurposed for biomedical and pharmacological applications, they are often subject to conditions different from those characteristic of their original biological environments. Non-canonical amino acids can impart properties that are inaccessible within canonical protein sequence space, and can thereby lead to improved or new functionality. We describe simple methods for global replacement of canonical amino acids by their non-canonical counterparts in recombinant proteins made in high yield in bacterial expression hosts. These methods can be used to engineer both chemical and physical properties of recombinant proteins.